2020
DOI: 10.1101/2020.09.16.20194316
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Graphene nanoplatelet and Graphene oxide functionalization of face mask materials inhibits infectivity of trapped SARS-CoV-2

Abstract: Recent advancements in bidimensional nanoparticles such as Graphene nanoplatelets (G) and the derivative Graphene oxide (GO) have the potential to meet the need for highly functional personal protective equipment (PPE) that confers increased protection against SARS-CoV-2 infection and the spread COVID-19. The ability of G and GO to interact with and bind microorganisms as well as RNA and DNA provides an opportunity to develop engineered textiles for use in PPE. The face masks widely used in health care and oth… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 42 publications
1
22
0
1
Order By: Relevance
“…By leveraging their affinity towards viral particles, nanomaterials can be used to entrap viral particles and improve infiltration rates on face masks [4] , [6] , [7] . As a recent example, De Maio et al reported that graphene nanoplatelets- and GO-based integration into face masks and other PPE enhances their protection efficacy significantly increasing their protection against the SARS-CoV-2 virus [8] . Finally, these materials have been shown to be effective antiviral drug delivery systems for various viral-based pathologies [100] , [101] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By leveraging their affinity towards viral particles, nanomaterials can be used to entrap viral particles and improve infiltration rates on face masks [4] , [6] , [7] . As a recent example, De Maio et al reported that graphene nanoplatelets- and GO-based integration into face masks and other PPE enhances their protection efficacy significantly increasing their protection against the SARS-CoV-2 virus [8] . Finally, these materials have been shown to be effective antiviral drug delivery systems for various viral-based pathologies [100] , [101] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to extensive pre-clinical and clinical trials carried out for the design of drugs and vaccines, various research efforts are being conducted to achieve better viral inactivation strategies outside the patients, such as the development of self-disinfecting surfaces or personal protective equipment (PPE). In this view, we and others have recently highlighted how nanotechnology and 2D nanomaterials can offer new approaches to cope with the COVID-19 pandemic and infectious diseases in general, including future pandemics [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] . The fact that lipid nanoparticle-based vaccines have already obtained approval by the US Food and Drug Administration and European Medical Agency shows that expertise and knowledge developed in the field of nanomedicine has enabled nanoparticle-based vaccine trials to take place in the fight against COVID-19 [18] , [19] , [20] , [21] .…”
Section: Introductionmentioning
confidence: 99%
“…In the context of graphene or GO incorporated in personal protective equipment (PPE), De Maio et al recently reported that GO could reduce SARS-CoV-2 infectivity in vitro. [76] However, the GO concentration range selected is excessive and not realistic for the purposes of antiviral therapeutics. Furthermore, given that there are different viral clades spreading among patient populations, it was important to evaluate the effectiveness of graphene or GO functionalized PPEs against multiple infectious viral genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, several antiviral face mask materials against SARS-CoV-2 have been recently proposed. However, all of these studies, some of them not peer-reviewed yet, propose expensive materials such as graphene [ 38 ], copper [ 39 ] or silver [ 40 ]. These antiviral composites are produced with complex and costly manufacturing processes, which render them non-viable for a global solution of the current COVID-19 pandemic strongly affecting both developed and underdeveloped countries.…”
Section: Introductionmentioning
confidence: 99%